Relationship Between DGAT1 Gene Polymorphism and Some Growth Traits in Anatolian Merino and Akkaraman Sheep - Tanış, AN; Keskin, İ (Journal of the Hellenic Veterinary Medical Society, 2025)
A strong correlation exists between growth traits and particular genes. Determining genotypes linked to advantageous morphometric features allows for selective breeding, promoting the establishment of flocks with preferred attributes. The DGAT1 gene is strongly connected to growth, meat quality, production, and carcass characteristics in sheep, making it a key target in research on growth efficiency and overall productivity. Investigated the relationship between the DGAT1 gene polymorphism and its variation and growth traits in 40 Anatolian Merino and 33 Akkaraman ewes in this study. Data on traits such as weight (six months weight (LW6), weaning weight (WW), birth weight (BW)), and body measurements were collected. Additionally, average daily weight gain (ADWG) and Kleiber ratios were computed. Using PCR-RFLP analysis with the AluI enzyme, three genotypes were identified, revealing polymorphisms: CC, CT, and TT. The analysis showed no statistically significant differences between genotypes and body measurements. These findings indicate that the DGAT1 gene is unlikely to be a suitable candidate for Marker-Assisted Selection (MAS) in Anatolian Merino and Akkaraman sheep, especially concerning traits associated with growth.